The Many Lives of Eddie Rickenbacker - Speno, Andrew (Biographies for young readers., 2020)
"The life story of a daredevil who became a war hero will fascinate adventurous young readers with its tales of survival. At age thirteen, following the death of his father, young Eddie dropped out of school and joined the workforce. Through a combination of smarts, hard work, and perseverance, Rickenbacker would grow up to become an automobile mechanic, a race car driver, a fighter pilot, an entrepreneur, a war hero, a business executive, and a staunch advocate for hard work and personal responsibility. Along the way he lived on the line between recklessness and courage. He survived dozens of accidents, coming close to death more than once. During the earliest years of American automobile racing, Rickenbacker was "the most daring and withal the most cautious driver" on the circuit. How could he have been both daring and cautious? The Many Lives of Eddie Rickenbacker invites young readers to decide for themselves as they follow him on his many hair-raising adventures."--